2021
DOI: 10.3390/ma14174926
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Design of a Clear Aligner Attachment to Induce Bodily Tooth Movement in Orthodontic Treatment Using Finite Element Analysis

Abstract: Clear aligner technology has become the preferred choice of orthodontic treatment for malocclusions for most adult patients due to their esthetic appeal and comfortability. However, limitations exist for aligner technology, such as corrections involving complex force systems. Composite attachments on the tooth surface are intended to enable active control of tooth movements. However, unintended tooth movements still occur. In this study, we present an effective attachment design of an attachment that can effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Considering that the intruded tooth was located in the most distal portion of the dentition, we chose the horizontal rectangular attachment with higher intrusion efficiency and set it on the adjacent tooth to obtain the best effect [23]. The effectiveness of rectangular attachments in tooth intrusion movement has been demonstrated in prior studies [24,25]. Moreover, only the intrusion side of the dentition was shown because the data on the non-intrusion side were insignificant and not the primary point of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the intruded tooth was located in the most distal portion of the dentition, we chose the horizontal rectangular attachment with higher intrusion efficiency and set it on the adjacent tooth to obtain the best effect [23]. The effectiveness of rectangular attachments in tooth intrusion movement has been demonstrated in prior studies [24,25]. Moreover, only the intrusion side of the dentition was shown because the data on the non-intrusion side were insignificant and not the primary point of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Attachments offer retention, help the transmission of force from clear aligners to the teeth, and can support clear aligners to correct various teeth movements such as correction of crown tipping, axial rotation, and tooth translation. 25 The three types of attachments subjected to FEA simulation were rectangular attachment, ellipsoid attachment, and pyramidal attachment. The results showed that the minimum and maximum von Mises stress did not significantly differ among the three attachment configurations.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth alignment treated by buccolingual inclination of upper and lower incisors can produce satisfied clinical results [ 34 ]. Previously, a clear aligner was not effective enough for a complex force system to result in an intended tooth movement [ 35 ], because it was not as strong as braces in producing adequate occlusal contacts, controlling teeth torque and retention [ 36 ]. So it is desired to improve the overall usability of clear aligners, in particular, in the aspects of materials and aligner design.…”
Section: Discussionmentioning
confidence: 99%